Metal fatigue : effects of small defects and nonmetallic inclusions - Murakami, Y. (Yukitaka), 1943- (Academic Press, 2019)
Metal fatigue is an essential consideration for engineers and researchers looking at factors that cause metals to fail through stress, corrosion, or other processes. Predicting the influence of small defects and non-metallic inclusions on fatigue with any degree of accuracy is a particularly complex part of this. Metal Fatigue: Effects of Small Defects and Nonmetallic Inclusions is the most trusted, detailed and comprehensive guide to this subject available. This expanded second edition introduces highly important emerging topics on metal fatigue, pointing the way for further research and innovation. The methodology is based on important and reliable results and may be usefully applied to other fatigue problems not directly treated in this book.